2020
DOI: 10.1504/ijmso.2020.108318
|View full text |Cite
|
Sign up to set email alerts
|

From the web of bibliographic data to the web of bibliographic meaning: structuring, interlinking and validating ontologies on the semantic web

Abstract: Bibliographic datasets have revealed good levels of technical interoperability observing the principles and good practices of linked data. However, they have a low level of quality from the semantic point of view, due to many factors: lack of a common conceptual framework for a diversity of standards often used together, reduced number of links between the ontologies underlying datasets, proliferation of heterogeneous vocabularies, underuse of semantic mechanisms in data structures, "ontology hijacking" (Feene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…However, certain crucial disadvantages will endure for years. First, it requires a sufficient amount of domain knowledge in the schemas of all relevant datasets, as well as a number of acceptable ontology vocabularies for semantic enrichment [58,59]. Second, it will significantly increase the complexity of the data as the ontologies created by various parties are challenged to be united in compliance with some common protocol.…”
Section: Interlinking Diverse Datamentioning
confidence: 99%
“…However, certain crucial disadvantages will endure for years. First, it requires a sufficient amount of domain knowledge in the schemas of all relevant datasets, as well as a number of acceptable ontology vocabularies for semantic enrichment [58,59]. Second, it will significantly increase the complexity of the data as the ontologies created by various parties are challenged to be united in compliance with some common protocol.…”
Section: Interlinking Diverse Datamentioning
confidence: 99%
“…Studies about library linked data projects have already identified important differences between the projects with regard to semantic interoperability issues, meaning the selected models, schemas and value vocabularies (Smith-Yoshimura, 2016Suominen & Hyvönen, 2017;Tallerås, 2018;Ullah, Khusro, Ullah, & Naeem, 2018). The existence of so many and different library linked datasets further raises the concern if the published datasets can be linked to one another, and if they can ultimately support the explore user task (H. Park & Kipp, 2019;Patrício et al, 2020;Suominen & Hyvönen, 2017;Tallerås, 2018).…”
Section: Basic Concepts -Relevant Academic Literaturementioning
confidence: 99%
“…Reports and studies regarding existing library linked data projects have raised concerns regarding the proliferation of bibliographic models and vocabularies (Hillmann, Coyle, Phipps, & Dunsire, 2010;Jett, Cole, Page, & Downie, 2016;Lovins & Hillmann, 2017;Patrício et al, 2020), the interoperability of bibliographic models with Linked Data principles (Dunsire, 2012;H. Park & Kipp, 2019;Peponakis, 2016;Willer & Dunsire, 2013), and the interoperability between the bibliographic models themselves (Cagnazzo, 2017;Hallo et al, 2016;Nillson, 2010;H.…”
Section: Studies By Scholarsmentioning
confidence: 99%
See 2 more Smart Citations